STUDY ON THE IMPORTANCE OF SECOND LINE ATTACK IN VOLLEYBALL GAME (GYMNASIUM, 2017)
The theme aims the progress of volleyball by aligning internal performance strategies to the modern game trends that are based on surprising the opponent. With this study we aim to make a critical analysis of the second line attack at the cadets volleyball team at the University National Center from CSU Tirgu-Mures. The sample of subjects were 12, all female. The research took place from 15 March to 20 May 2014. After implementing a model of training focused of the technical component of the second line attack and quantifying the performance indexes, significant differences were noted between the two trials. Thus, we conclude that an effective quality management of volleyball can be approaching official games through a tactical system oriented on using the second line attack on both phases of the game. This Paper is supported by the Sectorial Operational Programme Human Resources Development, financed from the European Social Fund and by the Romanian Government.